Results from the EISMINT model intercomparison: the effects of thermomechanical coupling - Payne, A. J.; Huybrechts, Philippe; Abe-Ouchi, A.; Calov, R.; Fastook, J. L.; Greve, R.; Marshall, S. J.; Marsiat, I.; Ritz, C.; Tarasov, L.; Thomassen, M. P. A. (2000)
This paper discusses results from the second phase of the European Ice sheet Modelling Initiative (EISMINT). It reports the intercompartison of ten operational ice-sheet models and uses a series of experiments to examine the implications of thermomechanical coupling for model behaviour. A schematic, circular ice sheet is used in the work which investigates both steady states and the response to stepped changes in climate. The major finding is that radial symmetry implied in the experimental design can, under certain circumstances, break down with the formation of distinct, regularly spaced spokes of cold ice which extended from the interior of the ice sheet outward to the surrounding zone of basal melt. These features also manifest themselves in the thickness and velocity distributions predicted by the models. They appear to be a common feature to all of the models which took part in the intercomparison, and may stem from interactions between ice temperature, flow and surface form. The exact nature of these features varies between models, and their existence appears to be controlled by the overall thermal regimne of the ice sheet. A second result is that there is considerable agreement between the models in their predictions of global-scale response to imposed climate change.